2011
DOI: 10.1186/1744-859x-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on hospitalization for assessment: a survey in Japan for a new forensic mental health system

Abstract: BackgroundIn Japan, hospitalization for the assessment of mentally disordered offenders under the Act on Medical Care and Treatment for the Persons Who Had Caused Serious Cases under the Condition of Insanity (the Medical Treatment and Supervision Act, or the MTS Act) has yet to be standardized.MethodsWe conducted a written survey that included a questionnaire regarding hospitalization for assessment; the questionnaire consisted of 335 options with 9 grades of validity for 60 clinical situations. The survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Similar to MSUs in the United Kingdom in terms of their capacity and human resources, Japanese inpatient facilities, in accordance with the MTSA in Japan[13], have more long-stay patients. However, this fact should be interpreted cautiously because some patients discharged from an MSU are transferred to a low secure unit, HSU, or prison.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MSUs in the United Kingdom in terms of their capacity and human resources, Japanese inpatient facilities, in accordance with the MTSA in Japan[13], have more long-stay patients. However, this fact should be interpreted cautiously because some patients discharged from an MSU are transferred to a low secure unit, HSU, or prison.…”
Section: Discussionmentioning
confidence: 99%
“…The panel has three possible disposition options: an order to hospitalize the offender for medical treatment, an order to care for the offender as an outpatient in the community, or a no‐treatment order. The offender is obliged to accept the special psychiatric care supplied by the designated medical facilities and to submit to continuous supervision by a rehabilitation coordinator working in a probation office (Shiina et al ., ).…”
Section: Findings (Table )mentioning
confidence: 97%
“…A total of 1,088 patients have been hospitalized into these designated facilities under the MTS Act over a five‐year period (July 15, 2005 to July 31, 2010). A total of 608 patients were discharged during those five years, after an average length of stay of 574 days (Shiina et al ., ).…”
Section: Findings (Table )mentioning
confidence: 97%
“…Temporary hospitalization of an offender for psychiatric examination and medical observation (usually for a few months) is called Hospitalization for Assessment (kantei-nyuin, HfA). A psychiatrist appointed by the court, named Examiner Psychiatrist, conducts a psychiatric evaluation of the offender and submits a report to the court [ 9 ]. A lawyer is appointed as an attendant to defend the offender during the judgment process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed in an attempt to optimize the HfA procedure [ 16 – 18 ]. We previously conducted a written questionnaire survey of leading Japanese forensic psychiatrists, to establish an expert consensus about how to deal with HfA cases [ 9 ]. We concluded that this consensus should be widely publicized among practitioners to ensure better management of offenders during HfA.…”
Section: Introductionmentioning
confidence: 99%